2021
DOI: 10.1002/cam4.3855
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival, adverse events, and economic burden in patients with chronic lymphocytic leukemia receiving systemic therapy: Real‐world evidence from the medicare population

Abstract: Background Information on overall survival (OS) and adverse events (AEs) in patients with chronic lymphocytic leukemia (CLL) is mostly available from clinical trials. We therefore conducted a population‐based retrospective cohort study to assess OS, incidence of AEs, and economic burden in real‐world practice among Medicare patients treated for CLL. Methods Patients with CLL receiving ≥1 systemic therapy from 2013 to 2015 were selected from the Medicare claims database and followed from the start of first obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…The 24-month OS rate among patients in the informCLL registry was 91% [ 27 ]. In another study [ 26 ], the 24-month OS rate was considerably lower at 69%; however, that analysis used Medicare data, and the median age of patients was notably higher than those in the registry analysis (76 years vs 69 years), and the patients had a median Charlson Comorbidity Index of 4, indicating a highly comorbid population. Although there was only one study in which 18-month and 30-month landmark estimates for OS was reported—the analysis of 457 patients from the informCLL registry—OS rates were similarly high at those timepoints, with 91% and 89% of patients estimated to be alive at 18 and 30 months, respectively [ 27 ].…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The 24-month OS rate among patients in the informCLL registry was 91% [ 27 ]. In another study [ 26 ], the 24-month OS rate was considerably lower at 69%; however, that analysis used Medicare data, and the median age of patients was notably higher than those in the registry analysis (76 years vs 69 years), and the patients had a median Charlson Comorbidity Index of 4, indicating a highly comorbid population. Although there was only one study in which 18-month and 30-month landmark estimates for OS was reported—the analysis of 457 patients from the informCLL registry—OS rates were similarly high at those timepoints, with 91% and 89% of patients estimated to be alive at 18 and 30 months, respectively [ 27 ].…”
Section: Resultsmentioning
confidence: 97%
“…Overall survival among patients with CLL treated with first-line ibrutinib was reported in one full-text article [ 28 ] and five abstracts [ 24 , 26 , 27 , 32 , 35 ]. Data were from multi-center medical records, Veteran’s Health Administration database, Medicare, SEER, and the informCLL registry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…45,46 Real-world studies investigate long-term safety and the impact of adverse events (AEs) on dose reductions and treatment discontinuations, 47 and provide important information on healthcare system costs. 48 Moreover, these studies are used to assess prognostic testing and treatment patterns, 49 and to collect data on specific CLL patient populations. 50 Other important information that can be obtained from RWE studies includes comparing real-world response rates to those described in clinical trials, 51 assessing the effectiveness of treatments in heavily pretreated high-risk patients with CLL, 52 or in different age groups, 53 evaluating the sequencing of targeted therapies in CLL, 54,55 as well as defining the impact of specific AEs.…”
Section: Real-world Evidence In Cllmentioning
confidence: 99%